Fabrication of a simple apparatus for the Seebeck coefficient measurement in high temperature region. (May 2017) - Singh, Saurabh; Pandey, Sudhir K.
Abstract: A simple apparatus for the measurement of Seebeck coefficient ( α ) in the temperature range 300–620 K has been fabricated. Our design is appropriate for the characterization of samples with different geometries like disk and rod shaped. The sample holder assembly of the apparatus has been designed in such a way that, single heater used for sample heating purpose is enough to provide a self maintain temperature gradient across the sample. The value of α is obtained without explicit measurement of temperature gradient. The whole apparatus is fabricated from the materials, which are commonly available, so that any part can be replaced in case of any damage. In order to calibrate the instrument, we have carried out Seebeck coefficient measurement on nickel metal and LaCoO3 compound. The values of α obtained for nickel and LaCoO3 sample using the designed set-up are found to be equal to the values reported in the literature.